Kemandirian Intelektual dan Kedisiplinan Siswa-siswi dalam Pembelajaran Pendidikan Agama Islam (Studi Eksplorasi SMA Muhammadiyah Susukan Kabupaten Semarang) - Millatana, Aufiy; Nursikin, Mukh (Attractive : Innovative Education Journal, 2024)
This research is to determine the independence and discipline of students in learning PAI at SMA Muhammadiyah Susukan, Semarang Regency. Independence and discipline are the keys to the success of a learning activity. This study used a qualitative approach, in obtaining data researchers used interviews, observation, and documentation. Data analysis in this study includes data reduction, data presentation, and drawing conclusions. The results of this study conclude that students' intellectual independence in learning PAI at SMA Muhammadiyah Intellectual independence and student discipline in learning PAI at SMA Muhammadiyah Susukan. The intellectual independence of students at Muhammadiyah High School Susukan is reflected through activities including: literacy reading the Qur'an, midday and midday prayers in congregation, and cults, student work titles in the form of call to prayer, tartil, qiro'ah, performing arts dance and painting. e. Efforts to increase student independence and discipline in learning PAI. Efforts made at SMA Muhammadiyah Susukan in increasing student independence, especially in PAI learning include: using models in learning activities, providing fun material, giving appreciation or praise. Efforts to improve student discipline in learning PAI at Muhammadiyah High School Susukan through the following: implementing class rules, punishments or sanctions and giving. (3) Inhibiting and supporting factors in increasing students' intellectual independence and discipline in PAI learning at Muhammadiyah High School Susukan include: Inhibiting factors in increasing students' intellectual independence as follows: student background, lack of books provided, internal factors, namely laziness, lack of communication from the teacher. Keywords: Intellectual Independence, Intellectual Discipline, Educational Learning